(untitled) (Academicia Globe: Inderscience Research, 2021)
Under the leadership of President Shavkat Mirziyoyev, it is important to pay more attention to our youth and involve them in culture, arts and sports, to develop skills in the use of information and communication technologies, to promote reading among the younger generation in our country. five important initiatives have been put forward to ensure attention and implementation.